Terapia assistida por cães na aprendizagem de adolescentes com deficiência intelectual - Bunduki, Thais Oliveira [UNESP]; Milanez, Simone Ghedini Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The realization of this project is justified by the fact of Dogs Assisted Therapy in the education of adolescents with intellectual disabilities in schools is a very important topic. This project aims to assess the efficacy of assisted therapy dogs, analyzing the benefits of the animal's presence during the activities developed by them. This is a comparative study, in which a teenager participated in the activities assisted by the dog and the other does not. Data on consultations mediated Dogs Assisted Therapy revealed that its use is very beneficial as it promotes motivation to assisted and increases the bond between the therapist and the patient.

A realização deste projeto justifica-se pelo fato da Terapia Assistida por Cães na educação de adolescentes com deficiência intelectual nas escolas ser um tema de extrema relevância. Este projeto tem por objetivo avaliar a eficácia do uso da terapia assistida por cães, analisando os benefícios da presença do animal durante as atividades desenvolvidas por eles. Este é um estudo comparativo, no qual um adolescente participou das atividades assistidas pelo cachorro e o outro não. Os dados relativos aos atendimentos mediados pela Terapia Assistida por Cães revelaram que seu uso é muito benéfico, uma vez que promove motivação ao assistido e aumenta o vínculo entre o terapeuta e o paciente.
Keywords: Dogs assisted therapy; Intellectual disabilities; Special education; Terapia assistida por cães; Deficiência intelectual; Educação especial